Soil organic carbon in seasonally dry Tropical Forests: state of knowledge and effects of forest age under clear cutting on soil quality of the Caatinga - Oliveira, Ramona Rodrigues Amaro de (Departamento de Ciências Agronômicas e Florestais - DCAF, 2026)
Anthropogenic pressures have intensified environmental challenges in tropical dry ecosystems, altering landscape dynamics, degrading soils, and compromising soil quality. The objective of this study was to evaluate the state of knowledge on soil carbon fractions in Seasonally Dry Tropical Forests (SDTF) and to assess the effects of post-clear-cutting forest age on soil characteristics and soil organic carbon (SOC) dynamics in the municipality of Angicos, Rio Grande do Norte, Brazil. The first chapter investigated the structure of scientific production on soil organic carbon fractions and soil health in SDTF between 2000 and 2024 through a state-of-the-knowledge assessment, based on searches in the Web of Science and Scopus databases, careful article selection, and the construction of scientific maps using VOSviewer and RStudio. This approach allowed the description of the temporal evolution of 57 publications, as well as collaboration networks, the most influential journals, and the main research themes. Scientific production increased after 2008, with influence concentrated in a few countries and journals, and a scarcity of studies integrating different soil properties. The second chapter evaluated areas under forest management through clear-cutting in the Caatinga (with 7, 11, 12, and 15 years of regeneration) and a Caatinga area within the same property with similar characteristics but no history of forest cutting, used as a reference (time 0). The study assessed how different post-clear-cutting ages influence soil carbon content and fractions, as well as soil chemical, physical, and biological attributes and land use and cover dynamics. Soil samples were collected at depths of 0–10 cm and 10–20 cm, and chemical and physical attributes, soil organic carbon fractions, enzymatic activities (β-glucosidase and arylsulfatase), micromorphological characteristics, and land use and cover dynamics were analyzed. Data were subjected to multivariate statistical analyses (PCA and Pearson correlation), Singular Spectrum Analysis (SSA), and regression analysis. The results indicated intense losses of carbon and nutrients in the first years after forest cutting, faster recovery of labile fractions compared to stable fractions, and insufficient 15-year cycles to ensure soil sustainability in sandy Entisols of the semi-arid region of Rio Grande do Norte. Furthermore, SSA suggests that SOC requires approximately 20 years to return to levels similar to those of the reference forest. Therefore, adjustments in clear cutting cycles, the adoption of conservation practices, and the prioritization of applied research are necessary to guide management practices aimed at maintaining soil quality and ecosystem functionality in the Caatinga.
Carbono orgânico do solo em florestas tropicais sazonalmente secas: estado atual do conhecimento e efeitos da idade da floresta sob corte raso na qualidade do solo da Caatinga.
Keywords: CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO; Soil organic matter; Sustainable forest management; Landscape change; Scientific knowledge; Matéria orgânica do solo; Gestão florestal sustentável; Mudança na paisagem; Conhecimento científico